PERANCANGAN APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSIS GANGGUAN AUTISME PADA ANAK BALITA DENGAN MENGGUNAKAN METODE DEMPSTER SHAFER - Rumengan, Bezaliel; Lubis, Chairisni; Tony, Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Expert System is one of Artificial Intelligence methods that uses the knowledge from an expert as a knowledge base. This Application is created to diagnose Autism Disorder for child under 5 years old with Dempster shafer method which user will have to input symptoms that the user feel to the application. This application can also give information about autism disorder that application cover. Based on the test result dempster shafer method worked well and produce good result in generating diagnosis about disorder matching the symptom given by the user which give a great result with diagnose accuracy for training data 95,45% and 93,33% for test data. Key words Dempster Shafer, Autism Disorder, Expert System